Abuse of Rights in Labor Relations: Concepts, Motives, Beneficial and Adverse Consequences - Melnyk, Kostiantyn; Tsesarsky, Felix; Zaitsev, Oleksii; Yatsenko, Tamara; Zaitsev, Oleksii (International Journal of Criminology and Sociology, 2022)
The article contains the studied issues of abuse of rights in labor relations: the concept of "abuse of rights in labor relations" has been defined, its motives, and beneficial and adverse consequences have been analyzed. The authors emphasize that "abuse of rights" as a legal fact arisen in specific life circumstances may have both beneficial and adverse social content. All this resulted from the fact that legislative practice does not keep up with real conditions of changing labor relations affected by dynamic circumstances of modern social and economic development of society. To develop new approaches to definition of the fundamental principles of labor law to ensure the rights of all participants in labor relations on the principles of equality before the law seems now to be very important. The solution to this problem is in formulation of a universal definition of the concept "abuse of rights in labor relations" like actions or inactions in the legal environment of labor law, based on antisocial motives of these actions (inactions), which do not coincide with motives officially indicated, resulting in adverse social consequences such as discrimination, oppression of labor rights of citizens and stateless persons, violation of the requirements for safe and healthy working conditions. In turn, according to the authors, actions or inactions beyond labor law, but based on positive social motives, resulting in beneficial social consequences such as labor rights of citizens and stateless persons for safe and healthy working conditions, production safety, environmental society, etc., shall not be considered as "abuse of rights" (but as "beneficial abuse of rights").